Gambaran Adverse Drug Reactions (Adrs) Pada Pasien Kanker Payudara yang Mendapatkan Adjuvant Endocrine Therapy (Aet) Tamoxifen dan Faktor-Faktor yang Mempengaruhinya di Rs Swasta Semarang Tahun 2023 - Kusumastuti, Maria Siska Triyuniar; Cholisoh, Zakky (Jurnal Ners, 2024)
The use of adjuvant endocrine therapy (AET) tamoxifen in the treatment of breast cancer has been associated with adverse drug reactions (ADRs). This study aims to assess the picture of ADRs in breast cancer patients receiving Tamoxifen Adjuvant Endocrine Therapy (AET) and the factors that influence it in Semarang private hospitals. This study was conducted with a cross-sectional design that was analyzed quantitatively and the sampling technique was carried out by purposive sampling. The inclusion criteria are adult breast cancer patients who receive Adjuvant Endocrine Therapy (AET) tamoxifen at least in 1 month, patients are willing to be respondents to fill out questionnaires by signing informed consent. Evaluation of the incidence of ADRs identified by the pharmacist. A total of 87 respondents experienced 18 types of ADRs. The three most common ADR events experienced by patients in the last 7 days were hormonal reactions to painful breasts (25.68%), hot or warm sensations in the upper body (chest, neck, face) (13.51%), vaginal dryness (10.14%). There is an incidence of ADRs in breast cancer patients receiving Adjuvant Endocrine Therapy (AET) tamoxifen. The three most common ADR events experienced by patients in the last 7 days were hormonal reactions to painful breasts (25.68%), hot or warm sensations in the upper body (chest, neck, face) (13.51%), vaginal dryness (10.14%). It is known that age, stage, and consumption of other drugs are not significantly associated with the incidence of ADR.